PENDIDIKAN KARAKTER DALAM PERSPEKTIF AL QUR’AN - Hamam Burhanuddin (AL-AUFA: JURNAL PENDIDIKAN DAN KAJIAN KEISLAMAN, 2019)
Character education consists of two words namely education and character. The meaning of character education according to Islam is a conscious effort made by educators to students to shape the personality of students who teach and shape morals, ethics, and a good sense of culture and noble character that foster students' ability to make good and bad decisions and realize goodness that in everyday life by means of education, teaching, guidance and training which is guided by the Qur’an and as-Sunna. The basis of character education in Islam is the Qur’an the character of the Prophet Muhammad. Character education is very important at this time because character will show who we really are, character will determine how someone makes decisions, character determines attitudes, words, and actions of someone, people who have good character, then the words and deeds will also be good, so all it will become a unified identity and personalize itself, making it easy to distinguish from other identities. The purpose of character education is to form a person of noble character because the noble character is the base of goodness. People of good character will soon leave goodness and leave badness. Implementation of character education in Islamic educational institutions varies greatly depending on the policies of these educational institutions.